Analisis Kekeliruan Berbahasa Indonesia dalam Tataran Fonologi oleh Penutur Asing pada Kanal YouTube IShowSpeed - Muhammad Nazar Al Azhari (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Several pronunciation faults in the Indonesian language and one in the Javanese language are to be examined in this study, which is based on a phonological analysis of the YouTube channel "IShowSpeed." In order to compare the key features, this study uses a qualitative research design and data analysis techniques based on the articulatory phonetic matching approach, which combines sophisticated comparison linking techniques with basic determining elements (PUP) procedures. (HBSP). Videos from one of the live broadcasts on the "IShowSpeed" YouTube channel served as the study's data source. This study employed the observation and note-taking method as its data gathering strategy. Data reduction, data display, and conclusion drawing were all part of the data analysis technique. The results of this study demonstrate that Speed made 10 phonological errors. Some of these errors include 1 instance of phoneme deletion, 4 instances of phoneme addition, and 5 instances of phoneme alteration. The phonological errors made by Speed are very common because they are made by a beginner or a foreign speaker. Therefore, The findings of this study are intended to be used as a case study in BIPA learning as well as an illustration of faults in the field of phonological studies.